The Comprehensible Input Theory in Second Language Acquisition: Origin, Development and Evaluation - Chen, Shangyun (Journal of Educational Theory and Practice, 2026)
Krashen’s Comprehensible Input (i+1) Hypothesis is the core of his language acquisition theory, which originated in the late 1970s and early 1980s, aiming to explain the process of second language acquisition. This theory is based on previous language acquisition research and absorbs relevant theories from psychology and pedagogy, as well as Vygotsky’s sociocultural theory and Chomsky’s linguistic theory. Krashen’s theory emphasizes that language acquisition is a natural and subconscious process and highlights the importance of language input. The theory is still applied today; scholars have put forward new insights based on Krashen’s theory, with both consistencies and contradictions. It has not only changed educational practitioners’ practices in language teaching and curriculum design but also provided an important theoretical tool for understanding the complex process of second language acquisition.